1981
DOI: 10.1021/bi00519a024
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and kinetic examination of protein stabilization by glycerol

Abstract: The effect of concentrated glycerol on the thermal transitions of chymotrypsinogen and ribonuclease has been examined by differential spectrophotometry at 293 and 287 mm, respectively. It was found that for both proteins addition of glycerol raises the transition temperature, the increase in Tm being greater for ribonuclease than for chymotrypsinogen. This increase in the free energy of denaturation appears to reflect primarily a decrease in the entropy change. Analysis in terms of the Wyman linkage equation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
232
1
4

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 475 publications
(253 citation statements)
references
References 54 publications
16
232
1
4
Order By: Relevance
“…4B). While a function for the AAV5-glycerol interaction is unknown, a protein-stabilizing role for glycerol is well established (74,75). The localization of this ligand between two surface loops which differ in structure between AAV5 and the other AAVs, VR-VII and HI, with VR-VII being significantly larger than in the other viruses (Fig.…”
Section: Fig 2 Aav Capsid Surfaces (A Cmentioning
confidence: 99%
“…4B). While a function for the AAV5-glycerol interaction is unknown, a protein-stabilizing role for glycerol is well established (74,75). The localization of this ligand between two surface loops which differ in structure between AAV5 and the other AAVs, VR-VII and HI, with VR-VII being significantly larger than in the other viruses (Fig.…”
Section: Fig 2 Aav Capsid Surfaces (A Cmentioning
confidence: 99%
“…The cosolvent glycerol is preferentially excluded from the protein-solvent interface and can therefore induce a decrease in volume and compressibility of the protein interior [13]. It has been suggested that a balance between repulsion of glycerol from hydrophobic surfaces of the protein and interaction with polar regions, is in fact the origin of the well known stabilizing effect of glycerol [18,19]. Besides its function as a viscogen glycerol can also induce structural changes in a protein, but this may arise from either an indirect effect of glycerol on the hydration layer or the same repulsion mechanism [20].…”
Section: Discussionmentioning
confidence: 99%
“…De fato, vários trabalhos têm mostrado que os osmólitos estabilizam proteínas contra caotrópicos 36,37,58,59 , acidez 54,58,60,61 , diminuições 5,58 ou elevações na temperatura 58,60,62,63 , altas pressões 58 e baixa atividade de água 52,58 . Os osmólitos elevam a energia livre de desnaturação das proteínas, de tal forma que ΔG°N oDo > ΔG°N wDw 32,[64][65][66][67][68] . A explicação mais ampla e aceita para esse efeito foi fundamentada na interação preferencial da água com a proteína 21 , com base na teoria das funções de Wyman 69,70 , que permitiu construir a relação (16) onde K é a constante de equilíbrio de uma reação reagente produto, que é modulada por um ligante x; -ν x representa a associação de um ligante ao reagente e ao produto; e T, P e a j são, respectivamente, temperatura, pressão e atividade do componente j.…”
Section: Equilíbrio De Estabilização De Proteínas Em Soluções Aquosasunclassified
“…Esta competição é vencida pela água, ou seja, a proteína prefere ligar-se às moléculas de água que ao osmólito, que é então preferencialmente excluído da superfície da proteína, segundo um efeito que foi denominado de efeito solvofóbico 32,64,65 ou osmofóbico 71 . Este efeito pode ser explicado pela maior afinidade pela água que pela mistura osmólito-água dos grupos apolares 64,65 e do esqueleto peptídico 68 da proteína. De qualquer forma, a competição gerada entre o osmólito e a água pela proteína eleva a energia livre de hidratação tanto do estado N (ΔG°N wNo ) quanto do estado D (ΔG°D wDo ) da proteína.…”
Section: Equilíbrio De Estabilização De Proteínas Em Soluções Aquosasunclassified
See 1 more Smart Citation